An alarming trend: Change in the risk profile of patients with ST elevation myocardial infarction over the last two decades. (1st December 2017) - Mentias, Amgad; Hill, Elizabeth; Barakat, Amr F.; Raza, Mohammad Q.; Youssef, Dalia; Banerjee, Kinjal; Sawant, Abhishek C.; Ellis, Stephen; Murat Tuzcu, E.; Kapadia, Samir R.
Abstract: Background: Coronary artery disease (CAD) is the leading cause of mortality around the world. We sought to study changes in the risk profile of patients presenting with ST elevation myocardial infarction (STEMI). Methods: We retrospectively studied all patients presenting with STEMI to our center between 1995 and 2014. Patients were divided into four quartiles, 5 years each. Baseline risk factors and comorbidities were recorded. Sub-analysis was done for patients with established CAD and their household incomes. Results: A total of 3913 patients (67.9% males) were included; 42.5% presented with anterior STEMI and 57.5% inferior STEMI. Ages were 64 ± 12, 62 ± 13, 61 ± 13 and 60 ± 13 in the four quartiles respectively. Obesity prevalence was 31, 37, 38 and 40% and diabetes mellitus prevalence was 24, 25, 24 and 31%, while hypertension was 55, 67, 70 and 77%, respectively, p  < 0.01 for all. Smoking prevalence was 28, 32, 42 and 46, p  < 0.01. When subgroup analysis was done for patients with history of CAD, prevalence of smoking, obesity, diabetes and hypertension significantly increased across the four quartiles. When patients were divided to four groups based on household income (poor, low middle, middle and high income), prevalence of diabetes, hypertension, smoking and obesity were significantly higher in patients with low income. Conclusion: Despite better understanding of cardiovascular risk factors and more focus on preventive cardiology, patients presenting with STEMI over the past 20 years are getting younger and more obese, with more prevalence of smoking, hypertension, and diabetes mellitus. This trend is greater in the lower income population.